Perancangan Harga Pokok Produksi Excel pada Usaha Daur Ulang Plastik dengan Metode Full Costing - Putri, Dyah Puspitasari Sunaryo; Dewanti, Rully Nur (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Plastic waste is a global issue that requires sustainable solutions. PT. XYZ, a plastic recycling company based in Tangerang, currently uses manual methods for calculating the cost of goods manufactured (COGM), which may lead to cost inaccuracies. This study aims to design an Excel-based COGM calculation system using the full costing method, which includes raw material costs, direct labor, and factory overhead. The research employs a qualitative approach with a descriptive method. It was conducted at a plastic recycling company in Tangerang. The focus of this study is the Excel-based COGM system for plastic recycling businesses using the full costing method. Data were collected through primary sources (observations, interviews, documentation) and secondary sources from related literature. The data were analyzed descriptively. The results show that the Excel-based design improves accuracy, transparency, and efficiency in cost calculations compared to the previous manual method. This new system provides a more realistic picture of production costs and can serve as a basis for pricing decisions, cost control, and performance evaluation. The practical implications of the system include reducing human error in calculations, accelerating cost analysis, enabling the company to set more competitive selling prices, and ultimately increasing overall profitability.